Explaining the impact of new parties in the Western European party systems. Issue 4 (2nd October 2019) - Emanuele, Vincenzo; Chiaramonte, Alessandro
ABSTRACT: In recent years, and particularly following the impact of the "great recession", Western European party systems have undergone profound change. New parties have emerged and been successful, thus radically changing the structure of inter-party competition. So far, research on new parties has been mainly conducted from party-level and election-centred perspectives. Here, instead, we focus on party system innovation (PSInn), meaning the impact of new parties on Western European party systems, and on the factors that explain such impact, by adopting a systemic perspective and taking into account all the arenas where inter-party competition takes place (i.e. elections, parliaments and governments). For this purpose, this article relies on an original dataset on the performances of new parties in terms of votes, seats, and ministerial posts, covering about 350 elections and 670 governments in 20 countries, over the period 1945–2017. The results of the analysis show a notable increase in PSInn over the last decade, in particular with regard to the electoral and parliamentary arenas. Moreover, data show that PSInn in the electoral and the parliamentary arenas is mainly predicted by turnout change, while in the governmental arena is instead driven by the country's economic performance.